Estudo não clínico do efeito ansiolítico símile e antidepressivo símile do álcool piperonílico em camundongo - Gonzaga, Thallita Karla Silva do Nascimento (2020)
Neurobehavioral alterations reach considerable amount of worldwide population, among these disorders, anxiety and depression that are cause of psychological and physical limitations. And many medicine plants have been a target on psychopharmacological studies to produce new psychoactive drugs with less adverse effects. Piperonal is derived from safrol, and obtained from Piper hispidinervum has proven antibacterial activity, prevention of liver steatosis, insulin resistance and possible anxiolytic-like activity. Piperonyl alcohol is obtained from Piper. Spp. Species or from piperine biometabolism in rats. Therefore the main goal of this study is to investigate the piperonyl alcohol influence on central nervous system and its anxiolytic-like and antidepressant-like effects, through the evaluation of neurobehavioral alterations on mice and the elucidation of its mechanism of action. The compound in initial tests presented stimulant effect on pharmacological screening and its letal dose 50 was defined above 5.000mg/kg characterizing, previously, a low toxicity substance. The investigation of anxiolytic activity was performed at cross elevated test and hole board test, it was observed that the compound decreased the anxiogenic behavior caused by the apparatus in the mices at the chosen doses, and 50mg/kg it is the better dose. The methods to investigate antidepressant-like activity it was forced swin test , that decreased the immobility time at the doses of 25mg/kg and 50mg/kg and the tail suspension test that the dose of 50mg/kg showed significant effect on immobility time. To validate the results obtained and prove that the antidepressant like effect of piperonyl alcohol it is not a stimulant effect on central nervous system it was realized the open field test, the animals treated with piperonyl alcohol did not show locomotor alterations compared to control groups, results confirmed by rota-rod test, where the animals also did not show any locomotor alteration induced by drug test. The last test performed it was forced swim test to investigate the involvement of serotoninergic via at anxiolytic like and antidepressant like effect, then it was used ketanserin 1mg/kg , as 5-HT2 receptor antagonist, it was verified an increase of immobility time, abolishing the piperonyl alcohol effect. The immobility time of the group treat with ketanserin 1mg/kg / piperonyl alcohol 50mg/kg it was similar to control group, characterizing a possible involvement of serotoninergic system at anxiolytic like and antidepressant like effect of drug. It is possible to conclude front of obtained results that the piperonyl alcohol showed significant antidepressant like effect and reduced anxiogenic behavior in the mice